2002
DOI: 10.1046/j.1365-2591.2002.00559.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and macroscopic study of maxillary molars with two palatal roots

Abstract: Clinicians should be aware of uncommon anatomical variations in maxillary molars. The majority of maxillary first molars have three roots and four canals. Maxillary molars may have two canals in the palatal root.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 10 publications
1
64
0
4
Order By: Relevance
“…Extensive literature [9,45], clinical study [2,8,30,41,46,47,48,49] and case reports are presented on maxillary first molars (Table 2). Among the root canal anomalies of maxillary molars, the least frequent appears to be that of palatal root.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive literature [9,45], clinical study [2,8,30,41,46,47,48,49] and case reports are presented on maxillary first molars (Table 2). Among the root canal anomalies of maxillary molars, the least frequent appears to be that of palatal root.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies and case reports regarding the unusual anatomical variation and configuration of the root canal system in maxillary first molars have been illustrated. These include a single root canal in a single root [11,12], two root canals [13], five root canals [14,15,16,17,18], six root canals [19,20,21], seven root canals [22], eight root canals [1], Cshaped canals [23,24], fusion of two buccal roots [25], fusion of two buccal roots with two palatal roots [26], four roots including an additional palatal root [27][28][29][30][31][32][33] and also five roots [31]. There are innumerable case reports and clinical studies of maxillary first molar on varied root canal morphology.…”
Section: Introductionmentioning
confidence: 99%
“…26 Following this, many other studies and case reports have shown the difficulty in assessing the root and root canal morphology of the upper molar and its variation in root fusion from diagnostic radiographs. [26][27][28][29][30] In all these case reports and studies it is shown that root variation in the upper molar can be suspected if there is any variation from normal root morphology in the diagnostic radiograph, and this can be confirmed during access cavity preparation by identifying the extra root canal orifice or by taking additional radiographs. In accordance with these studies and case reports, many practitioners in this study were not able to detect the normal root morphology and its variation in upper molar radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…Bu yüzden hekimin kök kanal anatomisi ve morfolojisini eksiksiz bilmesi uygulayacağı tedavinin başarısı için gereklidir. 1 Diğer taraftan tanı amacıyla çekilen radyografiler de hekime kök kanal anatomisini ve olabilecek varyasyonları anlayabilmesinde yardımcıdır. 2,3 Genellikle alt ikinci büyük azı dişleri 2 köklü ve 3 kanallıdır.…”
Section: Introductionunclassified